Authentication of Marantodes pumilum (Blume) Kuntze: A Systematic Review - Ibrahim, Ida Syazrina; Mohd Said, Mazlina; Mohammad Zainoor, Noraida; Jamal, Jamia Azdina (Frontiers in Pharmacology, 2022)
Herbal medicinal product (HMP) consists of complex phytochemical constituents that vary based on various factors that substantially produce different pharmacological activities and possible side effects. Marantodes pumilum (Blume) Kuntze (M. pumilum) or Kacip Fatimah is one of the most popular Malay traditional herbs and widely recognized for its medicinal use. Many studies have been conducted focusing on the identification of bioactive substances, pharmacological and toxicological activities in its specific varieties but less comprehensive study on M. pumilum authentication. Lack of quality control (QC) measurement assessment may cause different quality issues on M. pumilum containing products like adulteration by pharmaceutical substances, substitution, contamination, misidentification with toxic plant species, which may be detrimental to consumers health and safety. This systematic literature review aims to provide an overview of the current scenario on the quality control of herbal medicinal products as determined by pharmacopoeia requirements specifically for M. pumilum authentication or identification. A systematic search for peer-reviewed publications to document literature search for M. pumilum authentication was performed using four electronic databases; Web of Science, PubMed, Scopus and ScienceDirect for related studies from January 2010 to December 2021. The research studies published in English and related articles for identification or authentication of M. pumilum were the main inclusion criteria in this review. A total 122 articles were identified, whereby 33 articles met the inclusion criteria. Macroscopy, microscopy, chemical fingerprinting techniques using chromatography, spectroscopy and hyphenated techniques, and genetic-based fingerprinting using DNA barcoding method have been used to identify M. pumilum and to distinguish between different varieties and plant parts. The study concluded that a combination of approaches is necessary for authenticating herbal raw materials and products containing M. pumilum in order to assure the quality, safety, and efficacy of marketed herbal products, particularly those with therapeutic claims.